Loss of Fumarate Hydratase and Aberrant Protein Succination Detected With S-(2-Succino)-Cysteine Staining to Identify Patients With Multiple Cutaneous and Uterine Leiomyomatosis and Hereditary Leiomyomatosis and Renal Cell Cancer Syndrome. (December 2016) - Llamas-Velasco, Mar; Requena, Luis; Adam, Julie; Frizzell, Norma; Hartmann, Arndt; Mentzel, Thomas
Abstract : Aims: Hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome is an autosomal dominant disorder caused by heterozygotic germline mutations in fumarate hydratase (FH) with incomplete penetrance, and clinically challenging to diagnose. Immunohistochemical stainings may favor an earlier diagnosis. Methods and Results: The authors have tested 31 smooth muscle neoplasms. Ten of the 13 lesions from patients with HLRCC syndrome showed negative FH staining. Most sporadic piloleiomyomas presented strongly positive FH staining although 5 cases were negative. Sensitivity of FH staining in our series is 83.3% but specificity is 75%. Anti-S-(2-succino)-cysteine (2SC) showed the opposite intensity staining pattern and showed great correlation with anti-FH (rho spearman = −0.797). Anti-2SC staining increased the diagnostic accuracy in 19% of the cases. Limitations: The main limitation of this study is the lack additional clinical data to further classify the cases as the case inclusion was histopathological. Conclusions: Negative FH staining could indicate a high risk of HLRCC but it could also suggest the presence of a syndrome in up to 25% of sporadic cases. Thus, when there is a doubtful case, anti-2SC may be added to exclude the syndrome if a negative staining is found.